The Araceae of Malesia III: Bakoa - Wong Sin, Yeng; Boyce, P.C (Malaysian Nature Society, 2012)
A review of the genus Bakoa P.C.Boyce & S.Y.Wong is presented. Three species are recognized, of which one (B. nakanotoi S.Y.Wong) is described as new to science. A key to species is provided and all species are illustrated.